2007
DOI: 10.1200/jco.2006.09.6297
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of Fluorodeoxyglucose Positron Emission Tomography to Other Functional Imaging Techniques in the Evaluation of Metastatic SDHB-Associated Pheochromocytoma and Paraganglioma

Abstract: With a sensitivity approaching 100%, [18F]FDG-PET is the preferred functional imaging modality for staging and treatment monitoring of SDHB-related metastatic PGL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
231
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(250 citation statements)
references
References 30 publications
14
231
1
4
Order By: Relevance
“…In all patients, we found a full correspondence between the number of lesions revealed by radiologic imaging (CT) and the pathological uptakes revealed by 18 F-FDG PET/CT. The majority of the ambiguous lesions revealed by CT were confirmed as positive on 18 F-FDG PET/CT; our findings are quite similar to what was observed in other studies about PH [7,8,13,14] confirming 18 F-FDG PET/CT accuracy even in restaging and follow-up. Other studies have also demonstrated that 18 F-FDG PET/CT is superior to 123 I-MIBG SPECT for evaluating treatment response, considering its more accurate spatial resolution and the possible presence of MIBG-confounding treatment [19,20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In all patients, we found a full correspondence between the number of lesions revealed by radiologic imaging (CT) and the pathological uptakes revealed by 18 F-FDG PET/CT. The majority of the ambiguous lesions revealed by CT were confirmed as positive on 18 F-FDG PET/CT; our findings are quite similar to what was observed in other studies about PH [7,8,13,14] confirming 18 F-FDG PET/CT accuracy even in restaging and follow-up. Other studies have also demonstrated that 18 F-FDG PET/CT is superior to 123 I-MIBG SPECT for evaluating treatment response, considering its more accurate spatial resolution and the possible presence of MIBG-confounding treatment [19,20].…”
Section: Discussionsupporting
confidence: 91%
“…The role of 18 F-FDG PET/CT in staging patients affected by PH is well established as these tumors have shown high glucose metabolism [9][10][11][12][13][14][15][16], although, unfortunately, a correlation between 18 F-FDG uptake and malignant potential or prognosis has never been demonstrated [7,8]. In particular, a study reported that there is not a significant difference between 18 F-FDG uptake in benign and malignant PH and that the uptake is not influenced by the secretory status [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compression fracture was common in our cases (66.7%). 18F-FDG-PET/CT has been used for diagnosis of various neoplasms including MPG [26]; it is also the most effective method to evaluate the metastasis of PGs [10]. There is no doubt that a preoperative biopsy can facilitate surgery protocol formulation, especially for the solitary lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of MIBG scintigraphy had reported to be 86-92% 1,11,12 and may show false negative in pheochromocytoma with small size or weak function. In this patient, the finding that noradrenaline and adrenaline concentrations in the right adrenal vein were 60 and 2.8 times higher compared with those in the left adrenal vein along with the MRI findings strongly suggested the presence of Abbreviations: Ad, adrenaline; DA, dopamine; Nad, noradrenaline; PAC, plasma aldosterone concentration.…”
mentioning
confidence: 99%